Temporal changes in spatial variation: partitioning the extinction and colonisation components of beta diversity. (14th March 2021) - Tatsumi, Shinichi; Iritani, Ryosuke; Cadotte, Marc W.
Abstract: The last two decades have witnessed unprecedented changes in beta diversity, the spatial variation in species composition, from local to global scales. However, analytical challenges have hampered empirical ecologists from quantifying the extinction and colonisation processes behind these changing beta diversity patterns. Here, we develop a novel numerical method to additively partition the temporal changes in beta diversity into components that reflect local extinctions and colonisations. By applying this method to empirical datasets, we revealed spatiotemporal community dynamics that were otherwise undetectable. In mature forests, we found that local extinctions resulted in tree communities becoming more spatially heterogeneous, while colonisations simultaneously caused them to homogenise. In coral communities, we detected non‐random community disassembly and reassembly following an environmental perturbation, with a temporally varying balance between extinctions and colonisations. Partitioning the dynamic processes that underlie beta diversity can provide more mechanistic insights into the spatiotemporal organisation of biodiversity. Abstract : The last two decades have witnessed unprecedented changes in beta diversity (spatial variation in species composition) from local to global scales. Here, we develop a novel numerical method to additively partition the temporal changes in beta diversity into components that reflect local extinctions and colonisations.